Annual report on surveillance for avian influenza in poultry and wild birds in Member States of the European Union in 2021. (15th September 2022) - ,; Aznar, Inma; Baldinelli, Francesca; Stoicescu, Anca; Kohnle, Lisa
Abstract: European Union (EU) Member States (MSs) are required to carry out surveillance for avian influenza (AI) in poultry and wild birds and notify the results to the responsible authority. In addition, Iceland, Norway, Switzerland and the United Kingdom (Northern Ireland) also implement ongoing surveillance programmes to monitor incursions of avian influenza viruses (AIVs) in poultry and wild birds. EFSA received a mandate from the European Commission to collate, validate, analyse and summarise the data resulting from these AI surveillance programmes in an annual report. The present report summarises the results of the surveillance activities carried out in MSs and the aforementioned countries in 2021. Overall, 24, 290 poultry establishments (PEs) were sampled, of which 27 were seropositive for influenza A(H5) and 4 for A(H7) viruses. Seropositive PEs were found in 10 MSs and, as per previous years, the highest percentages of seropositive PEs were found in establishments raising waterfowl game birds and breeding geese. Out of these 31 seropositive PEs, 3 tested positive by polymerase chain reaction (PCR) for influenza A(H5) viruses: 1 for highly pathogenic avian influenza virus (HPAIV), 1 for low pathogenic avian influenza virus (LPAIV) and 1 with unknown virus pathogenicity. In addition, 16 countries reported PCR test results from 1, 858 PEs which did not correspond to the follow‐up testing of a positive serology event (e.g. in some PEs, PCR tests were used for screening). Sixty‐five of these PEs in 10 MSs were found positive for AIVs. Apart from poultry, 31, 382 wild birds were sampled, with 2, 314 wild birds testing positive for HPAIVs by PCR. Twenty‐two countries reported HPAIV‐positive wild birds and most positive samples were identified as highly pathogenic avian influenza (HPAI) A(H5N8) virus. In addition, 328 wild birds tested positive for LPAIVs of the A(H5/H7) subtypes and 362 wild birds tested positive for non‐A(H5/H7) subtype AIVs.